2021
DOI: 10.1002/ctm2.478
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomal miR‐19b‐3p facilitates M2 macrophage polarization and exosomal LINC00273 secretion to promote lung adenocarcinoma metastasis via Hippo pathway

Abstract: Numerous reports have elucidated the important participation of exosomes in the communication between tumor cells and other cancer‐related cells including tumor‐associated macrophages (TAMs) in microenvironment. However, the interchange of exosomes between tumor cells and TAMs in the progression of lung adenocarcinoma (LUAD) remains largely enigmatic. Herein, we discovered that LUAD cells induced the M2 polarization of TAMs and the M2‐polarized macrophages facilitated LUAD cell invasion and migration and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 82 publications
(164 reference statements)
3
68
0
2
Order By: Relevance
“…In recent years, exosomes have attracted much attention as mediators of intercellular communication in the TME [ 21 , 22 ]. Mounting basic studies have reported that stromal-cell-derived exosomes play a critical role in regulating tumorigenesis and TME remodeling by transferring diverse contents such as miRNA, DNA, and cytokines [ 23 25 ]. Importantly, exosomes have been shown to be an important means through which macrophages interact with tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, exosomes have attracted much attention as mediators of intercellular communication in the TME [ 21 , 22 ]. Mounting basic studies have reported that stromal-cell-derived exosomes play a critical role in regulating tumorigenesis and TME remodeling by transferring diverse contents such as miRNA, DNA, and cytokines [ 23 25 ]. Importantly, exosomes have been shown to be an important means through which macrophages interact with tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, activated YAP induced the transcription of RNA-binding motif protein encoded on the X chromosome (RBMX). By binding to miR-19b-3p, RBMX facilitated the packaging of miR-19b-3p into LUAD cell-derived exosomes [ 99 ]. Collectively, the miR-19b-3p/LINC00273/YAP feedback loop contributed to the communication between lung cancer cells and tumor-associated macrophages.…”
Section: The Crosstalk Between Yap/taz and Micrornasmentioning
confidence: 99%
“…Furthermore, mature DC exosomes can promote osteogenic differentiation and improve bone regeneration by transporting miRNA-335 (miR-335) in thighbone-deficient thymic rats [ 46 ]. Moreover, tumor-derived exosomes can promote the polarization of M2 macrophages, while exosomes carrying miRNA-19b-3p (miR-19b-3p) can promote lung cancer metastasis via the Hippo pathway [ 47 ]. Finally, exosomes from hepatocellular carcinoma (HCC) cells can promote tumorigenesis by secreting sonic hedgehog (Shh) protein [ 48 ], which is closely related to both embryonic development and histogenesis in mammals.…”
Section: Exosome Functionmentioning
confidence: 99%